(untitled) (Semiárida, 2020)
The following study intends to inform about the way the dairy farmer of La Pampa province develops his work and which can be the base for an extension strategy The surfaces of the plots that form the different regions are very similar with the tendency to find the greater extension in the dairy region of the south. The amount of subdivision of the fields presents a high proportion among those of 10 and 20 subplots. In the north and center region a significant average of dairies produces less than 1200 I daily. In the south 40% of the dairies produce 1200 and 2400 I daily, average, that in the north region, is reached only by the 10% of farms. In the 55% of the dairies in the north and south regions 25% do not count with cooling equipment. The relation between dairy cows and total cows does not show important evidences of variation in the three regions. With regards to total cows in the central and the south region, the 60% of the farmers and 30% dairy farmer own less than 90 cows. A greater number of cows is owned in the south, centre and north region represent a proportion of 50,25 and 12% respectively. The way the soil is used indicates the differences between the regions and is related to climatic conditions. In the north region it was found that a great number of farms do not have winter annual forage crops. In the north, centre and south regions the 45, 50 and 80% of the farms respectively do not have summer forage crops. In all three regions of stock to ensilage does not exist in a 70% of them. Finally, on the central region almost the 30% of the farmers do not have lucern perennial pasture (Medicago sativa). Generally, similar patterns of distribution according to the indicators used in this study were observed for the three dairy regions. These indicators show a high degree of heterogeneity between dairy farms within each region, which, in turn leads to a high variability within a region and homogeneity of these indicators variables between regions.